1996
DOI: 10.1016/s0008-6363(96)00155-1
|View full text |Cite
|
Sign up to set email alerts
|

Vagal nerve stimulation increases right ventricular contraction and relaxation and heart rate

Abstract: Objective: To determine the effects of vasoactive intestinal peptide, released from the right and left vagal nerves, on ventricular contraction, relaxation, and heart rate. Methods: The muscarinic and P-adrenergic receptors were blocked with atropine and propranolol, and afterload was controlled in 48 anesthetized, open-chest mongrel dogs. Experiments were performed in the absence (Series 1, 10 dogs) and in the presence (Series 2, 22 dogs) of a controlled heart rate and prior to and after the administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The stimulation protocol was repeated at the same frequencies but for a longer duration of 1 min after exposing the atria to atropine (3 mol/l) for 3 min. The reason for the longer electrical stimulation after atropine is that the vagal tachycardia is known to require a longer duration of stimulation [3,7] .…”
Section: Experimental Protocol For Vagus Attached Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulation protocol was repeated at the same frequencies but for a longer duration of 1 min after exposing the atria to atropine (3 mol/l) for 3 min. The reason for the longer electrical stimulation after atropine is that the vagal tachycardia is known to require a longer duration of stimulation [3,7] .…”
Section: Experimental Protocol For Vagus Attached Preparationmentioning
confidence: 99%
“…Nevertheless, the presence of a vagal tachycardia in a species may be a relatively good indicator of the potential physiological contribution of VIP to vagal cardiac function. It is well established that the tachycardia is easily obtainable in the dog [1,3] and it has been shown in the same species that VIP plays a role in the maintenance of normal sinus arrhythmia [4] . However, the exact role of VIP in the vagal regulation of the rat heart has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac vagal nerve stimulation in dogs during muscarinic and β-adrenergic receptor blockade, caused increased contractile force in the right atrium [4] and the right ventricle [5,6], whereas no significant [5][6][7]. It was also shown that intracoronary infusion of the VIP antagonist [4Cl-D-Phe',Leu"(]VIP could significantly reduce the vagal-induced increases in right atrial\right ventricular contractility, suggesting that VIP was the mediator of this positive inotropic effect in the right atrium and ventricle [4,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…The dose of VIP receptor antagonists used in the present study, 100 Ìg i.c. given to dogs with an average weight of 19.5 kg, was effectively just above 5 mg kg -1 , a concentration which is generally larger than that used by other investigators [10][11][12][15][16][17].…”
Section: Discussionmentioning
confidence: 73%